2021
DOI: 10.3390/ijerph18041576
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Successful Smoking Cessation According to Age Group: Findings of an 11-Year Korea National Survey

Abstract: Previous studies suggest that factors related to smoking cessation may vary with age. This study examined the factors affecting smoking cessation by age among Korean adult male smokers using data from the Korea National Health and Nutrition Examination Survey from 2007 to 2018 (excluding 2013). Logistic regression analyses were used to investigate various factors associated with smoking cessation in three different age groups. Out of a total of 15,492 individuals, 31.5% of the 3523 individuals aged 19–39 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 37 publications
7
32
1
Order By: Relevance
“…The findings can be summarized as follows: 1) smoking cessation rates in the CKD group remained relatively stable during the study period, whereas those in the non-CKD group tended to increase; 2) fewer factors were significant in quitting smoking in the CKD group than in the non-CKD group; and 3) the interaction effects between the two groups revealed that regular exercise was the only factor associated with quitting in the CKD group. As stated above, smoking cessation rates in participants without CKD tended to increase over the study period; this has been previously observed in Korean male smokers (Table 1) 30 . During the study period, cessation rates in the CKD group did not seem to increase but were higher than those in the non-CKD group throughout the study.…”
Section: Discussionsupporting
confidence: 78%
“…The findings can be summarized as follows: 1) smoking cessation rates in the CKD group remained relatively stable during the study period, whereas those in the non-CKD group tended to increase; 2) fewer factors were significant in quitting smoking in the CKD group than in the non-CKD group; and 3) the interaction effects between the two groups revealed that regular exercise was the only factor associated with quitting in the CKD group. As stated above, smoking cessation rates in participants without CKD tended to increase over the study period; this has been previously observed in Korean male smokers (Table 1) 30 . During the study period, cessation rates in the CKD group did not seem to increase but were higher than those in the non-CKD group throughout the study.…”
Section: Discussionsupporting
confidence: 78%
“…Although Kim and Cho. [15] reported that married adult males were more successful in cessation of smoking compared with the single people; we did not determine a significant difference regarding the smoking and marital status. This may be due to the high number of married participants in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Socioeconomic variables were unable to be included despite literature suggested some contribution towards smoking cessation. 24,28 Secondly, the outcome measured (smoking cessation) was measured based on self-report without biochemical verification. This method tends to be skewed in smoking behaviour due to subject recall bias and social desirability bias.…”
Section: Discussionmentioning
confidence: 99%